Effect of Coronavirus Disease 2019 on CO2 Emission in the World - Sahar Safarian; Runar Unnthorsson; Christiaan Richter (Aerosol and Air Quality Research)
Abstract In order to decrease spreading of Coronavirus disease 2019 (COVID-19) over the world, the activity of many industries has declined, several flights were cancelled and so many people staying home that made drop in fuel consumption in road transport. As industries, transport networks and businesses have closed down, it has brought a sudden drop in carbon emissions. Hence, in this paper, a simple estimation model is developed by using some excel features to assess the reduced CO2 emissions in March 2020. Then this indicator is calculated for 3 scenarios which are based on this disease situation worldwide and therefore based on different reduction percent of fossil fuels consumption in various sectors over year 2020. In scenario 1, it is assumed the number of infected people increasing but it is before peak region. In this zone, the measures to slow the rate of infection would be similar till end of year. In scenario 2, the infectious growth rate in the world reaches to peak region. Hence, the protective measures would be extended. As a result, industries activities and various kinds of transportations will be probably reduced much more in comparison with scenario 1. In scenario 3, it is assumed the growth rate begins to fall and it is after peak region. In this zone, the intervention and protective measures would be lessened toward scenario 1. So, industries activities and transportations will be likely increased in compare to other scenarios. The results show that CO2 emissions worldwide in March 2020 has been 7% lower than the monthly average of this parameter in 2019 as consequence of COVID-19. Moreover, carbon emission through 2020 has been estimated to be 34.4, 32.4 and 35.3 Gton based on scenarios 1, 2 and 3, respectively. It is worth to mention that based on these three scenarios, this indicator in 2020 will be approximately the same as 2011, 2008 and 2012.